Sequential bargaining in a New Keynesian model with frictional unemployment and staggered wage negotiation - Gregory de Walque; Olivier Pierrard; Henri Sneessens; Raf Wouters (National Bank of Belgium, 2009)
We consider a model with frictional unemployment and staggered wage bargaining where hours worked are negotiated for each period. The workers' bargaining power in the working time negotiations affects both unemployment volatility and inflation persistence. The closer to zero this parameter, (i) the more firms tend to adjust on the intensive margin, reducing employment volatility, (ii) the lower the effective workers' bargaining power for wages and (iii) the more important the hourly wage in determining the marginal cost. This set-up produces realistic labour market figures together with inflation persistence. Distinguishing the probability to bargain the wage rate for existing and new jobs, we show that the intensive margin helps reduce the new entrants' wage rigidity required to match observed unemployment volatility.
Keywords: E31; E32; E52; J64; 330; DSGE; Search and Matching; Nominal Wage Rigidity; Monetary Policy; Lohnrigidität; Tarifverhandlungen; Geldpolitik; Lohnstückkosten; Dynamisches Gleichgewicht; Theorie; USA